Eksistensi Direktorat Jenderal Penegakan Hukum Lingkungan Hidup dan Kehutanan dalam Penanganan Kasus Pencemaran Lingkungan oleh Pabrik Pengolahan Kelapa Sawit di Riau - Risyan Putri Maharani; Dhamara Kusuma Swastika Ratri; Destina Balqis Anggiyanti (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Indonesia faces complex environmental problems due to management that is out of balance with economic and population growth. One prominent case is the alleged environmental pollution by PT SIPP in Bengkalis, Riau, involving unauthorized waste disposal and damage to a wastewater treatment plant (WWTP). This study aims to describe the role of the Directorate General of Environmental and Forestry Law Enforcement (DG Gakkum LHK) in handling the case. Using a qualitative approach and descriptive method, data was collected through a literature study covering environmental pollution regulations and similar cases. The DG Gakkum LHK, which falls under the Ministry of Environment and Forestry, plays an important role in environmental law enforcement through technical policies, supervision, investigation, and application of administrative and criminal sanctions. Since its establishment in 2015, DG Gakkum has improved law enforcement with a multi-instrument approach and cooperation with civil society and relevant law enforcement. In the PT SIPP case, DG Gakkum took decisive action by arresting two company officials and revoking the business license. This research highlights the important role of DG Gakkum in maintaining environmental quality and the sustainability of natural resource management, as well as the challenges faced in enforcing environmental law in Indonesia. Efforts to increase public and business awareness about the importance of environmental protection as well as effective cooperation between government agencies and the community are key in addressing environmental issues holistically.